The 1988 civil service reform and governmental performance in Nigeria - Egwurube, Joseph Ogaba (1990)
The weakness in Nigeria's 1988 civil service program lies in the fact that the reform geared towards development only tackled the structural problems and left the program aspect of the government untouched. This article critically examines and questions the premise on which the reform was based and concludes that the move will not lead to appreciable improvements in the government. The reform measure has duly consolidated vast powers on the President in the determination of needs and the allocation and mobilization of resources.
Keywords: Civil service reform -- Nigeria; Political reform -- Nigeria